2015
DOI: 10.5194/aab-58-99-2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the level and duration of feeding restriction on carcass components of broilers

Abstract: Abstract. The effects of the restriction of the advised daily feed intake (ADFI) during 1 or 2 weeks on broiler body weight (BW) and carcass composition were studied. A total of 150 1-day-old male broilers (Ross-308) were randomly allotted to a control and four experimental treatments with three replicates per treatment. Broilers were subjected to a feeding restriction equal to 75 and 50 % of ADFI, either for a 7-or a 14-day period, between the 7th and 14th and 7th and 21th day of age, respectively. The BW and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 32 publications
7
31
2
Order By: Relevance
“…Survival rate was similar among the experimental groups, showing that FR had no harmful effect and correlate to the findings of other experiments (1,5,20) . However, published results indicated that FR increased survival rate due to less sudden death, ascites and skeletal disorders (24,25) .…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Survival rate was similar among the experimental groups, showing that FR had no harmful effect and correlate to the findings of other experiments (1,5,20) . However, published results indicated that FR increased survival rate due to less sudden death, ascites and skeletal disorders (24,25) .…”
Section: Resultssupporting
confidence: 89%
“…In accordance with the current results, immune response against NDV and IBD at 30 th d of age was found to be lower in the FR group than the control group (34) . In addition, FR at 75 and 50 % of daily feed intake during 7-14 or 7-21 d of age did not affect absolute and relative weight of spleen and thymus, but groups on FR at 75 and 50 % for 7 d significantly increased Fabricius bursa compared to their counterparts groups (20) . Similarly, nutritional status had a crucial role in immunity and under-nutrition can negatively affect immune function (29,31) .…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Feed restriction is used to retard growth performance of fast growing birds, in particular, in alternative systems of production, which require long growth phases (Govaerts et al, 2000;Jahanpour et al, 2015;Nielsen, Litherland, & Noddegaard, 2003;Soltanmoradi et al, 2014). Nutritionists and researchers have reported that in broilers, physical feed restriction for a short time at an early age decreases abdominal fat, improved growth, and feed efficiency; furthermore, the performance of birds in restricted and unrestricted groups is similar at marketing age (Farghly, Abd El-Hack, Alagawany, Saadeldin, & Swelum, 2018a;Farghly Alagawany & Abd El-Hack, 2018b;Naji, Al-Ani, Manati, & Mukhlis, 2003).…”
Section: Introductionmentioning
confidence: 99%